Effect of Therapy on Radiographic Progression in Axial Spondyloarthritis: A Systematic Review and Meta‐Analysis. Issue 5 (1st April 2020) - Karmacharya, Paras; Duarte‐Garcia, Ali; Dubreuil, Maureen; Murad, M. Hassan; Shahukhal, Ravi; Shrestha, Pragya; Myasoedova, Elena; Crowson, Cynthia S.; Wright, Kerry; Davis, John M.
Abstract : Objective: To investigate the effect of therapies on radiographic progression in patients with axial spondyloarthritis (SpA). Methods: A comprehensive database search for studies assessing radiographic progression in axial SpA (particular treatment versus no treatment of interest) was performed. Study‐specific standardized mean differences in treatment outcomes at 2 and ≥4 years were estimated and combined using random‐effects models. Results: Twenty‐four studies in patients with axial SpA were identified, of which 18 involved tumor necrosis factor inhibitors (TNFi), 8 involved nonsteroidal antiinflammatory drugs (NSAIDs), and 1 involved secukinumab. Spinal radiographic progression, as measured by the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS), was not significantly different between TNFi‐treated and biologics‐naive patients at 2 years (mSASSS difference −0.73 [95% confidence interval (95% CI) −1.52, 0.12], I 2 = 28%) and ≥4 years (mSASSS difference −2.03 [95% CI −4.63, 0.72], I 2 = 63%). Sensitivity analyses restricted to studies with a low risk of bias showed a significant difference in spinal radiographic progression between TNFi‐treated and biologics‐naive patients at ≥4 years (mSASSS difference −2.17 [95% CI −4.19, −0.15]). No significant difference in spinal radiographic progression was observed between NSAID‐treated and control patients (mSASSS difference −0.30 [95% CI −2.62, 1.31], I 2 = 71%) or between secukinumab‐treated and biologics‐naive patients (mSASSS difference −0.34 [95% CI −0.85, 0.17]). With regard to treatment differences in patients with nonradiographic axial SpA or in patients with radiographic progression measured using the sacroiliac joint score, an insufficient number of studies were available for analysis. Conclusion: Although no significant protective effect of TNFi treatment on spinal radiographic progression was seen over the course of 2 years or ≥4 years in patients with axial SpA, our analysis restricted to studies with a low risk of bias showed a protective effect of TNFi after ≥4 years. Therefore, long‐term TNFi exposure might confer beneficial effects on spinal radiographic progression in axial SpA. No difference in radiographic progression at 2 years was seen in either the NSAID or secukinumab treatment groups compared to their controls. Future studies should explore the effects of biologic treatment on radiographic progression, as well as the effects of long‐term biologics exposure, in patients with early axial SpA or those with nonradiographic axial SpA.